Addressing Willful Blindness: A Multi-Domain Framework for Enhancing Legal Accountability and Fairness - Cecep Mustafa (Jurnal Hukum dan Peradilan, 2024)
Willful blindness, a legal doctrine in which individuals deliberately avoid knowledge to escape accountability, plays a significant role in the adjudication of crimes such as corporate fraud, financial misconduct, and sexual assault. However, current research has not fully examined its strategic misuse or provided a comprehensive analysis of its application across different legal contexts. This study bridges these gaps by introducing a Multi-Domain Analytical Framework to evaluate the concept's impact, strategic use, and broader implications in both criminal and civil cases. Empirical findings reveal that willful blindness is often employed to evade legal responsibility, undermining justice and compromising the fairness of legal outcomes. The study further demonstrates the inadequacy of existing legal standards and evidentiary requirements in addressing this issue. To counter these challenges, the research proposes targeted policy reforms designed to strengthen accountability, enhance evidentiary clarity, and improve the overall fairness and effectiveness of the legal system. In conclusion, willful blindness remains a critical and manipulative tool with profound implications for justice and accountability. This study highlights the necessity of reforming legal frameworks to mitigate the strategic exploitation of willful blindness. By setting the stage for further research and policy development, the findings contribute to the ongoing evolution of a more just and equitable legal system capable of addressing the complexities of modern legal challenges.